2021
DOI: 10.1523/jneurosci.0227-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Flexible versus Fixed Spatial Self-Ordered Response Sequencing: Effects of Inactivation and Neurochemical Modulation of Ventrolateral Prefrontal Cortex

Abstract: Previously, studies using human neuroimaging and excitotoxic lesions in non-human primate have demonstrated an important role of ventrolateral prefrontal cortex (vlPFC) in higher order cognitive functions such as cognitive flexibility and the planning of behavioral sequences. In the present experiments, we tested effects on performance of temporary inactivation (using GABA receptor agonists) and dopamine D 2 and 5-HT 2A receptor blockade of vlPFC via local intracer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Although motor or sensory deficits can be ruled out, because they would result in a location-independent decrease in behavioral performance, more complex network effects beyond the EC cannot be excluded. These could arise from alterations to activity in the prefrontal cortex, which was previously shown to be involved in spatial tasks requiring cognitive flexibility 65 , 66 (but also see ref. 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although motor or sensory deficits can be ruled out, because they would result in a location-independent decrease in behavioral performance, more complex network effects beyond the EC cannot be excluded. These could arise from alterations to activity in the prefrontal cortex, which was previously shown to be involved in spatial tasks requiring cognitive flexibility 65 , 66 (but also see ref. 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Humans with schizophrenia show impairments of spatial learning (Bakker et al, 2020), error monitoring (number of rule-breaking errors), efficiency (time and number of moves to completion), and show perseverations (Snyder et al, 2008) which can improve with dopaminergic and cholinergic drugs (Lieberman et al, 2013; Pietrzak et al, 2009; Pietrzak et al, 2010). Maze learning also involves the recall of spatial sequences, which involves the hippocampus (Buzsaki & Tingley, 2018), ventrolateral prefrontal cortex (Axelsson et al, 2021) and the dorsolateral prefrontal cortex (Mushiake et al, 2006; Saito et al, 2005). It shares similarities to the path learning of nonhuman primates controlling cursors (Mushiake et al, 2001), and spatial relational learning of rodents in the Morris Water Maze, which is linked to the hippocampal system and to cholinergic modulation as muscarinic compounds reverse deficits in spatial learning and memory (Popiolek et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The CR task has the same requirements as the Delayed Recognition Span task that depends on prefrontal cortex and its dopaminergic and noradrenergic functioning (Moore et al, 2005). It requires self-ordered search for a new target, which has been associated specifically with the ventral and lateral prefrontal cortex, but not the orbitofrontal or parietal cortex (Axelsson et al, 2021; Champod & Petrides, 2007; Walker et al, 2009), and in humans is causally supported by the inferior frontal gyrus (Chase et al, 2008). Deficits in self-ordered selection tasks are evident in humans diagnosed with attention-deficit-hyperactivity disorder (ADHD) (Dowson et al, 2004; Fried et al, 2015) and schizophrenia (Badcock et al, 2005; Pantelis et al, 1999), including first degree relatives and monozygotic twins of schizophrenic patients (Pirkola et al, 2005; Wood et al, 2003) even when they have no altered cognitive functioning (Joyce et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have shown that the contribution of vlPFC in marmosets to self-ordered response sequencing of spatial arrays is limited to when the arrays vary across trials, requiring flexible, goal-directed behavior for successful performance (Axelsson et al, 2021). In contrast, when the same spatial array was used across trials in a fixed version of the self-ordered sequencing task which encouraged more automated responding involving use of a restricted set of preferred response sequences, inactivation of the vlPFC was without effect (Axelsson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the marmoset monkey, fiber-sparing lesions to the combined lateral, orbital, and anteroventral regions of the PFC confirmed its role in self-ordered sequencing (Collins et al, 1998). Subsequently, this effect was localized to ventrolateral (vl)PFC, but not orbitofrontal cortex (Axelsson et al, 2021; Walker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%